THE ANALYSIS OF EXPORT COMPETITIVENESS ON INDONESIA'S PALM OIL, COCOA AND COFFEE COMMODITIES IN INTERNATIONAL MARKETS - Khairul Akbar; Sukardi; Ahmad albar tanjung; Sirojuzilam; Irsad (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Agricultural commodities that are competitive in the international market are divided into three groups: plantation, food crops and forestry. The commodities with the greatest export potential within the plantation sector are coconut, coffee, cocoa and palm oil. Nevertheless, the lack of processing facilities for palm oil, coffee and cocoa means that Indonesia is unable to export finished products to overseas markets. Furthermore, these three commodities also encounter processing issues that fail to meet international standards, which can diminish their competitiveness. This study aims to investigate the competitiveness of a country in the international market. The data utilized in this study is secondary data. Secondary data were obtained from the Central Statistics Agency, the FOA website, and the UNCOMTRADE website. The data analysis employed qualitative analysis methods to assess the competitive advantage of Indonesian coffee, cocoa and palm oil commodities in the international market. The results indicated that, overall, the competitiveness of these commodities to destination countries was satisfactory, as evidenced by the RCA value exceeding 1. However, the cocoa commodity exhibited a competitiveness score below 1 when assessed against the United States.